(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents the importance of innovative methods and their importance, as well as some examples of ways to interest students and explain the topic by using Case study, Problem question, Magic bag method, which is one of the innovative methods, by asking interesting problem questions.